Specialty Rice (Oryza sativa L.) for Health in Indonesia - Siti Dewi Indrasari (Fakultas Sains dan Teknologi UIN Sunan Kalijaga, 2022)
Rice (Oryza sativa L.) is the most nutritious staple food for most Indonesian people. The Ministry of Agriculture through the Agricultural Research and Development Agency has released about 300 rice varieties. Some of these varieties have advantages that are beneficial for health. The purpose of this article was to review literature describing the specialty rice varieties from Indonesia, with a particular focus on low Glycemic Index, high antioxidant and high mineral content. Low GI rice is one way of coping with diabetes mellitus (DM). Hyperlipidemia, diabetic syndrome, and cancer diseases could be prevented by consuming pigmented rice which is rich in antioxidants. Fortified rice could be used to overcome iron nutritional anemia and stunting problems. In order to to overcome nutritional and health problems in Indonesia, it is hoped that specialty rice could be used as a complementary program in the food diversification program that has been developed by the government. Specialty rice available in the market still has to pay attention to the quality class of the rice. Socialization about specialty rice needs to be conducted, and the availability of specialty rice opens up export opportunities.